Lean maintenance [reduce costs, improve quality, and increase market share] - Smith, Ricky (Elsevier Butterworth Heinemann, 2004)
What is "Lean?" Whether referring to manufacturing operations or maintenance, lean is about doing more with less: less effort, less space, fewer defects, less throughput time, lower volume requirements, less capital for a given level of output, etc. The need to provide the customer more value with less waste is a necessity for any firm wanting to stay in business, especially in today's increasingly global market place. And this is what lean thinking is all about. Lean Operations are difficult to sustain. More Lean Manufacturing Plant Transformations have been abandoned than have achieved true Lean Enterprise status. There are solid and recurring reasons for both of these conditions. The most significant of these reasons is that production support processes have not been pre-positioned or refined adequately to assist the manufacturing plant in making the lean transformation. And the most significant of the support functions is the maintenance operation, which determines production line equipment reliability. Moving the maintenance operation well into its own lean transformation is a must-do prerequisite for successful manufacturing plant - or any process plant - Lean Transformations. This Handbook provides detailed, step-by-step, fully explained processes for each phase of Lean Maintenance implementation providing examples, checklists and methodologies of a quantity, detail and practicality that no previous publication has even approached. It is required reading, and a required reference, for every plant and facility that is planning, or even thinking of adopting "Lean" as their mode of operation. * A continuous improvement strategy using new "lean" principles * Eliminate wasteful practices from your manufacturing or chemical processes, increasing the profitability of your plant * Save thousands of dollars a year on new equipment by keeping your existing equipment maintained using this revolutionary method.
Keywords: Production management.; Manufacturing processes.; Just-in-time systems.; elektronické knihy; electronic books